2017
DOI: 10.1103/physrevb.96.024414
|View full text |Cite
|
Sign up to set email alerts
|

Spin pumping into superconductors: A new probe of spin dynamics in a superconducting thin film

Abstract: Spin pumping refers to the microwave-driven spin current injection from a ferromagnet into the adjacent target material. We theoretically investigate the spin pumping into superconductors by fully taking account of impurity spin-orbit scattering that is indispensable to describe diffusive spin transport with finite spin diffusion length. We calculate temperature dependence of the spin pumping signal and show that a pronounced coherence peak appears immediately below the superconducting transition temperature T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(113 citation statements)
references
References 54 publications
8
103
2
Order By: Relevance
“…A monotonic decay of iSH voltages in the un-patterned and stripe-patterned samples across Tc (Fig. S5) confirms the absence of the superconducting coherence effect [44][45][46] in our system (i.e. metallic/conducting FM/SC bilayers).…”
Section: Section S5 Inverse Spin-hall Voltages In the Vicinity Of Tcsupporting
confidence: 73%
“…A monotonic decay of iSH voltages in the un-patterned and stripe-patterned samples across Tc (Fig. S5) confirms the absence of the superconducting coherence effect [44][45][46] in our system (i.e. metallic/conducting FM/SC bilayers).…”
Section: Section S5 Inverse Spin-hall Voltages In the Vicinity Of Tcsupporting
confidence: 73%
“…According to the theory, Gilbert damping is related to the interfacial s-d exchange interaction and the imaginary part of the dynamic spin susceptibility of the SC [20]. 2 Im ( )…”
Section: Resultsmentioning
confidence: 99%
“…After the growth, a thin Al2O3 layer (~ 10 nm) was deposited in situ as a capping layer to avoid sample degradation with air exposure. The Curie temperature of the GdN film was determined via the offset-magnetization as a function of the temperature using Gilbert damping [20]. Hence, the interfacial s-d exchange coupling provides the route to detect the spin dynamics of the NbN layer by measuring the magnetization dynamics of GdN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such systems charge and (non-collinear) spin transport are closely linked and need to be treated on the same footing. Recently there has also been increased interest to couple superconductors to magnets and find out how superconductivity affects the magnetization dynamics, [5][6][7][8][9][10][11][12][13][14][15] including thermally driven effects [16]. On the other hand, recent work has shown that a combination of magnetic and superconducting systems results to giant thermoelectric effects [17][18][19][20] coupling charge and heat currents.…”
mentioning
confidence: 99%